The young Lamfalussy: an empirical and policy-oriented growth theorist - Ivo Maes (National Bank of Belgium, 2009)
Alexandre Lamfalussy has been highly influential in the process of European monetary and financial unification. In this paper we will analyse the work of the "Young Lamfalussy" (from the mid 1950s to the mid 1960s). Lamfalussy started his career as an academic, focusing on growth theory and Belgian and European growth patterns in the post-war period. His work is still considered to be influential in the recent literature on Europe's post-war economic growth. It fits nicely into the Keynesian tradition: Lamfalussy's analytical frameworks were often inspired by Keynesian models, in his analysis he emphasised vicious and virtuous circles in the economy and, in his policy conclusions, he was a clear partisan of more planning. However, certain elements, typical also of Lamfalussy's later work, were already present, not least a strong European conviction and an eclectic approach towards economics, blending economic theory and empirical data beautifully to elucidate crucial policy problems
Keywords: B22; E60; 330; Lamfalussy; European growth patterns; Keynesian economics; Belgium; macroeconomic policy-making; Wachstumstheorie; Keynesianismus; Theorie; Belgien